How can we manage clinically significant interactions in hypertensive patients? - Perić, Aneta (Archives of Pharmacy, 2022)
Hypertensive patients, especially the elderly ones, are often exposed to polypharmacy. The aim of our study was to analyse potential drug-drug interactions (pDDIs) as well as potential adverse drug reactions (ADRs) among hypertensive patients. Moreover, we investigated the possibility of reducing pDDIs and potential ADRs with different treatment choices. We conducted a cross-sectional study during a two months period, which included all outpatiens with hypertension, treated in the Military Medical Academy in Belgrade, who had ≥2 medications prescribed. Lexicomp Interact was used for identification of pDDIs and potential ADRs. Treatment choices were explored according to patient’s characteristics, treatment guidelines and the interacting potential of drugs. Data were analysed using descriptive analysis and multiple logistic regression. A total of 350 patients were included in this study, with average age 75.3±11.5 years and 6.1±2.5 medications. The majority (86.0%) had at least one clinically significant pDDI, average was 3.78±3.90 (range 1-25). Suggestions for treatment change aimed mainly at eliminating drug duplications, reducing the use of thiazide diuretics, sulfonylureas, alpha-lipoic acid and pentoxiphylline and increasing the use of calcium-channel blockers, when appropriate. pDDIs would have decreased to 2.10 (2.52), p